Assessment of production and marketing constraints and value chain of sweet potato in the municipalities of Dangbo and Bonou. - EZIN, VINCENT; QUENUM, FLORENT JEAN-BAPTISTE (My University, 2018)
Background: Sweet potato [Ipomoea batatas (L.) Lam.] plays an important role in ensuring food security and incomes for local communities. It is particularly grown in southern region of Benin, and its production over the last few years has declined due to disease and severe pest infestation. Therefore, it was imperative to carry out this study to identify the main constraints related to the recent decline in sweet production and more specifcally analyzing the production and marketing constraints of sweet potato in the townships of Dangbo and Bonou. Results: The results of the survey revealed that many varieties of sweet potato were grown, mainly “Vobodouaho” (local name in Goun language), the most preferred variety by producers. Weedicides and insecticides were used to control weeds and insect pests, respectively. There was no efcient control methods against black rot, Alternaria blight, cylas spp., and caterpillar among the pathogens and insects that damaged sweet potato production in the study areas. The main constraints reducing sweet potato production in the townships of Dangbo and Bonou are: lack of adequate methods for controlling pest and diseases, lack of fnancial resources due to no access to credit, absence of modern equipment, scarcity and high cost of labor and absence of best methods for long-term storage. The average yield of sweet production per hectare ranged from 6.5 to 15.1 tons fresh matter/ha. The market value of sweet potato is still low at farmers’ level when compared to that of other stakeholders along the value chain. Conclusion: This study calls for the attention of public and private sectors and policy makers for more investment in sweet potato research. Avenues for further research on sweet potato have also been suggested.
Keywords: Actors in sweet potato; Horticulture; Limitations; Productivity; Revenue